On Generalized Holder's Inequality in Weak Morrey Spaces - Asyraf Wajih; Hendra Gunawan (Journal of the Indonesian Mathematical Society, 2020)
In this paper we reprove generalized Hölder's inequality in weak Morrey spaces.In particular, we get sharper bounds than those in \cite{gunawan2}. Thebounds are obtained through the relation of weak Morrey spaces and weakLebesgue spaces.